Phytochemical Profile, Antioxidant and Wound Healing Potential of Three Artemisia Species: In Vitro and In Ovo Evaluation - Daliana Minda; Roxana Ghiulai; Christian Dragos Banciu; Ioana Zinuca Pavel; Corina Danciu; Roxana Racoviceanu; Codruta Soica; Oana Daniela Budu; Delia Muntean; Zorita Diaconeasa; Cristina Adriana Dehelean; Stefana Avram (Applied Sciences, 2022)
Skin injuries, and especially wounds of chronic nature, can cause a major negative impact on the quality of life. New efficient alternatives are needed for wound healing therapy and herbal products are being investigated due to a high content of natural compounds with promising healing activity. For this purpose, we investigated three Artemisia species, Artemisia absinthium L. (AAb), Artemisia dracunculus L. (ADr) and Artemisia annua L. (AAn). Ethanolic extracts, containing different polyphenolic compounds, elicited strong antioxidant activities in the DPPH assay, comparable to ascorbic acid. Human ketratinocyte proliferation was stimulated and wound closure was enhanced by all three extracts at concentrations of 100 µg/mL. The Artemisia extracts modulated angiogenesis by increasing vessel formation, especially following treatment with A. annua and A. dracunculus, extracts with a significantly higher content of chlorogenic acid. Good tolerability and anti-irritative effects were also registered in ovo, on the chorioallantoic membrane (CAM). The three Artemisia species represent promising low-cost, polyphenol-rich, antioxidant, safe alternatives for wound care treatment.